Identification and functional analysis of a TEP gene from a crustacean reveals its transcriptional regulation mediated by NF-κB and JNK pathways and its broad protective roles against multiple pathogens. (May 2017) - Li, Chaozheng; Li, Haoyang; Xiao, Bang; Chen, Yonggui; Wang, Sheng; Lǚ, Kai; Yin, Bin; Li, Sedong; He, Jianguo
Abstract: Thioester-containing proteins (TEPs) are present in a wide range of species from deuterostomes to protostomes and are thought to be involved in innate immunity. In the current study, a TEP gene homologous to insect TEPs (iTEP) from the crustacean Litopenaeus vannamei, named LvTEP1, is cloned and functionally characterized. The open reading frame (ORF) of LvTEP1 is 4383 bp in length, encoding a polypeptide of 1460 amino acids with a calculated molecular weight of 161.1 kDa LvTEP1, which is most similar to other TEPs from insects, contains some conserved sequence features, including a N-terminal signal peptide, a canonical thioester (TE) motif, and a C-terminal distinctive cysteine signature. LvTEP1 is expressed in most immune-related tissues, such as intestine, epithelium, and hemocytes, and the mRNA level of LvTEP1 is upregulated in hemocytes after bacterial and viral challenges, indicating its involvement in the shrimp innate immune response. An expression assay in Drosophila S2 cells shows LvTEP1 to be a full-length secretory protein, and processed forms are present in the supernatant. Of note, only the processed form of LvTEP1 protein can bind to both the gram-negative bacterium Vibrio parahaemolyticus and the gram-positive bacterium Staphylococcus aureus in vitro, and its abundance can be induced after bacterial treatment. Moreover, knockdown of LvTEP1 renders shrimps more susceptible to both V. parahaemolyticus and S. aureus, as well as white spot syndrome virus (WSSV) infection, suggesting its essential defensive role against these invading microbes. We also observe that the expression of LvTEP1 is regulated in a manner dependent on both NF-κB and AP-1 transcription factors in naive shrimps and in vitro, suggesting that LvTEP1 could be poised in the body cavity prior to infection and thus play an important role in basal immunity. Taken together, our findings provide some in vitro and in vivo evidence for the involvement of LvTEP1 in shrimp innate immunity and provide some insight into its expression regulation mediated by multiple transcription factors or signaling pathways. Graphical abstract: Highlights: The first insect TEP like gene (LvTEP1) is identified from pacific white shrimp Litopenaeus vannamei. LvTEP1 can bind to both Vibrio parahaemolyticus and Staphylococcus aureus. LvTEP1 expression is regulated in a manner dependent on both NF-κB and AP-1. Shrimps with knockdown of LvTEP1 show more susceptible to bacterial and viral infection.